THE INFLUENCE OF RELATIONSHIP MARKETING DIMENSIONS ON CUSTOMER LOYALTY AT 'SAAT KOPI' CAFE SURABAYA: RELATIONSHIP MARKETING ON CUSTOMER LOYALTY - Yusup, Yusup; Zulvianasya GA, Divela; Suparno, Suparno (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2025)
This study investigates the influence of relational marketing dimensions trust, commitment, and communication on customer loyalty at Saat Kopi café in Surabaya, within the Food and Beverage (F&B) industry context. The research aims to understand how these dimensions foster customer retention in a competitive market. Data were collected through a survey of 30 customers who visit the café at least twice monthly, reside in Surabaya, and have a minimum high school education. Research techniques included observation, interviews, and questionnaires, with variables measured using a five-point Likert scale. Data quality was ensured through validity tests (Pearson correlation, significance < 0.05) and reliability tests (Cronbach’s Alpha > 0.6). Analysis procedures comprised descriptive statistics to summarize responses, multiple regression analysis to assess the simultaneous impact of relational marketing dimensions on loyalty, and T-tests to evaluate individual variable significance. The regression analysis incorporated classical assumptions (normality, multicollinearity, heteroscedasticity, and autocorrelation), with F-tests confirming the model’s overall significance and R² indicating the proportion of loyalty variance explained. Results reveal that trust, commitment, and communication positively and significantly influence customer loyalty, highlighting the effectiveness of relational marketing strategies in enhancing customer retention. These findings suggest that café management should prioritize building trust, fostering commitment, and maintaining effective communication to strengthen customer loyalty in the F&B sector. This study provides actionable insights for businesses aiming to improve customer relationships and loyalty.